Audio lingual strategies to teach basic english phonological production of the /F/, /V/, /S/ and /Z/ fricative sounds anibg 12th graders at Volcan Hight School - Caballero, Carol (David, Panamá : UDELAS, 2013)
Whit the appearance of the english language, a series of theories and methods hace arisen and which objective is to ease strategies and techniques for teaching english. Those methods based in the auditory development.
TABLE OF CONTENTS CHART INDEX FIGURE INDEX GRAPHIC INDEX INTRODUCTION CHAPTER I: ANTEDENTS AND STATEMENT OF THE PROBLEM CHAPTER II: THEORETICAL FRAMEWORK 2.1. Audio-lingual strtegies 2.1.1. What is tje audio-lingual method 2.1.2. The principles of audio-lingual method 2.1.3. Audio-lingual techniques to teach basic english 2.1.4. The use pf auditory drills to fix the pronunciation problem of the fricative /f/, /v/, /s/ and /z/ 2.2. Teaching of basic phonological production of the /f/, /v/, /s/ and /z/ fricative sounds 2.2.1. The fricative sounds 2.2.2. The difficult for the students to make the productions of the /f/, /v/, /s/ and /z/ fricative sounds 2.2.3. The productions of /f/, /v/, /s/ and /z/ fricative sounds CHAPTER III: METHODOLOGICAL ASPECTS CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY ANNEX
Incluye Table of contents
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; ENGLISH -- TESIS DE LICENCIATURA -- FONETICS; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA EN INGLÉS; AUDIO LINGUAL STRATEGIES; VOLCAN HIGHT SCHOOL